Coherent modulation of two-photon up-conversion from colloidal quantum dots by femtosecond laser. Issue 99 (23rd September 2015) - Xu, Cheng; Yao, Yunhua; Pu, Chaodan; Zhang, Shian; Liu, Xiaofeng; Qiu, Jianrong
Abstract : The coherent modulation of up-conversion PL of colloidal quantum dots by femtosecond laser has been experimentally and theoretically achieved, which proves that the fs pulse shaping technique can provide an effective method to control two-photon PL. Abstract : Using a pulse shaping technique, we demonstrate the modulation of two-photon luminescence (TPL) of quantum dots through phase and polarization of the excitation femtosecond (fs) laser. The dependance of TPL intensity on the π phase step position, square phase modulation time, and polarization angle of the fs laser is revealed.